ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN DEPOSITO MUDHARABAH PADA BANK UMUM SYARIAH PERIODE 2016-2020 - Aziz Septiatin (Jurnal Manajemen Dayasaing, 2022)
This study aims to analyze the effect of liquidity level, profit sharing ratio, and inflation on the growth of mudharabah deposits in Islamic commercial banks for the period 2016 – 2020. This study uses quantitative research. The sampling technique used purposive sampling method so that the samples obtained were 7 out of 14 BUS. The analytical method used is multiple regression analysis, but before being analyzed using regression analysis, it must meet the criteria for the classical assumption test. The results showed that the FDR variable had a negative and significant effect on the growth of mudharabah deposits, Profit sharing ratio had a positive and significant effect on the growth of mudharabah deposits, while inflation had no effect on the growth of mudharabah deposits. After being tested together, FDR, profit sharing ratio and inflation have a significant effect on the growth of mudharabah deposits. Keywords: FDR, Profit sharing ratio, inflation, mudharabah deposit growth